Global and regional health effects of future food production under climate change: a modelling study. Issue 10031 (7th May 2016) - Springmann, Marco; Mason-D'Croz, Daniel; Robinson, Sherman; Garnett, Tara; Godfray, H Charles J; Gollin, Douglas; Rayner, Mike; Ballon, Paola; Scarborough, Peter
Summary: Background: One of the most important consequences of climate change could be its effects on agriculture. Although much research has focused on questions of food security, less has been devoted to assessing the wider health impacts of future changes in agricultural production. In this modelling study, we estimate excess mortality attributable to agriculturally mediated changes in dietary and weight-related risk factors by cause of death for 155 world regions in the year 2050. Methods: For this modelling study, we linked a detailed agricultural modelling framework, the International Model for Policy Analysis of Agricultural Commodities and Trade (IMPACT), to a comparative risk assessment of changes in fruit and vegetable consumption, red meat consumption, and bodyweight for deaths from coronary heart disease, stroke, cancer, and an aggregate of other causes. We calculated the change in the number of deaths attributable to climate-related changes in weight and diets for the combination of four emissions pathways (a high emissions pathway, two medium emissions pathways, and a low emissions pathway) and three socioeconomic pathways (sustainable development, middle of the road, and more fragmented development), which each included six scenarios with variable climatic inputs. Findings: The model projects that by 2050, climate change will lead to per-person reductions of 3·2% (SD 0·4%) in global food availability, 4·0% (0·7%) in fruit and vegetable consumption, and 0·7% (0·1%) in red meat consumption. These changes will be associated with 529 000 climate-related deaths worldwide (95% CI 314 000–736 000), representing a 28% (95% CI 26–33) reduction in the number of deaths that would be avoided because of changes in dietary and weight-related risk factors between 2010 and 2050. Twice as many climate-related deaths were associated with reductions in fruit and vegetable consumption than with climate-related increases in the prevalence of underweight, and most climate-related deaths were projected to occur in south and east Asia. Adoption of climate-stabilisation pathways would reduce the number of climate-related deaths by 29–71%, depending on their stringency. Interpretation: The health effects of climate change from changes in dietary and weight-related risk factors could be substantial, and exceed other climate-related health impacts that have been estimated. Climate change mitigation could prevent many climate-related deaths. Strengthening of public health programmes aimed at preventing and treating diet and weight-related risk factors could be a suitable climate change adaptation strategy. Funding: Oxford Martin Programme on the Future of Food.